Transforming engagement: a case study of building intrinsic motivation in a child with autism - Emerson, Anne; Dearden, Jackie (Wiley, 2017)
This longitudinal case study of 10 year old girl with autism and severe communication impairment measures the impact of the MORE (Means, Opportunities, Reasons and Expectations) approach to enhancing engagement and communication proposed by Emerson and Dearden (2013a). Through detailed observation of video data over a period of 28 months engagement behaviours including interaction with adults and following adult directions increased whilst resistant behaviours such as kicking, hitting and pushing adults away decreased. Fluctuation between different ‘states’ demonstrated that the frequency and duration of engagement was influenced by the MORE approach and an emphasis on developing intrinsic motivation. In order to enable further efficacy research core features of the intervention and the changes in engagement over time are described.